Tribal worlds : critical studies in American Indian Nation building - Hosmer, Brian C., 1960-; Nesper, Larry, 1951- (Tribal worlds : critical studies in American Indian nation building., 2013)
This collection explores how Indigenous nationhood has emerged and been maintained in the face of aggressive efforts to assimilate Native peoples.